TYC 8606-2025-1: a mild barium star surrounded by the ejecta of a very late thermal pulse - Gvaramadze, Vasilii V.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We report the discovery of a spiral-like nebula with the Wide-field Infrared Survey Explorer and the results of optical spectroscopy of its associate